2018
DOI: 10.1111/papr.12687
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Idiopathic Supraorbital Neuralgia Using Percutaneous Pulsed Radiofrequency

Abstract: In conclusion, the results of our study demonstrate that for patients with refractory idiopathic supraorbital neuralgia, percutaneous pulsed radiofrequency may be an effective and safe treatment choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…It is worth noting that the patients in our study did not achieve excellent pain relief immediately after undergoing PRF, but rather required a median interval latency of 3 days (IQR,2-5; range,1-14 ) and two cases needed even more than 10 days to achieve satisfactory results. The interval latency is consistent with our previous studies on PRF for the treatment of supraorbital neuralgia, infraorbital neuralgia, and TN [32][33][34]. We assume the reason for the existence of a recovery period is because PRF could cause plastic changes in pain transmission pathways and result in slow neuromodulation, which would require longer time to take effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that the patients in our study did not achieve excellent pain relief immediately after undergoing PRF, but rather required a median interval latency of 3 days (IQR,2-5; range,1-14 ) and two cases needed even more than 10 days to achieve satisfactory results. The interval latency is consistent with our previous studies on PRF for the treatment of supraorbital neuralgia, infraorbital neuralgia, and TN [32][33][34]. We assume the reason for the existence of a recovery period is because PRF could cause plastic changes in pain transmission pathways and result in slow neuromodulation, which would require longer time to take effect.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, although PRF treatment under the guidance of CT increases the rate of successful punctures and decreases the incidence of complications caused by inaccurate punctures, patients are inevitably exposed to radiation energy which may lead to safety concerns. In recent years, ultrasonography has been proven to be a safer and easier imaging modality, without ionizing radiation [32,42]. Further investigations for the therapeutic efficiency of ultrasound-guided PRF operation on glossopharyngeal nerve is of great importance.…”
Section: Limitationsmentioning
confidence: 99%
“…The interval latency is consistent with our previous studies on PRF for the treatment of supraorbital neuralgia, infraorbital neuralgia, and TN. 33 – 35 We assume the reason for the existence of a recovery period is because PRF could cause plastic changes in pain transmission pathways and result in slow neuromodulation, which would require longer time to take effect. Therefore, after receiving PRF procedure, individual variations in posttreatment protocols should be taken into consideration, such as: adjusting oral analgesics to assist patients in getting through the recovery period without progression of pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ultrasonography has been proven to be a safer and easier imaging modality, without ionizing radiation. 33 , 43 Further investigations for the therapeutic efficiency of ultrasound-guided PRF operation on glossopharyngeal nerve are of great importance.…”
Section: Limitationsmentioning
confidence: 99%
“…We have reported the efficacy of PRF for treating idiopathic supraorbital neuralgia and refractory infraorbital neuralgia in recent years. [15][16][17] A small number of patients developed numbness in the area innervated by the target nerve and recovered soon after the onset of numbness. In the present study, trifling numbness along the maxillary nerve was observed in 6 patients.…”
Section: Discussionmentioning
confidence: 99%